2020
DOI: 10.1186/s12986-020-0434-8
|View full text |Cite|
|
Sign up to set email alerts
|

Oleic acid ameliorates palmitic acid induced hepatocellular lipotoxicity by inhibition of ER stress and pyroptosis

Abstract: Background: Pyroptosis is a novel programmed cell death. It is identified as caspase-1 dependent and characterized by plasma-membrane rupture and release of proinflammatory intracellular contents inculuding IL-1 beta and IL-18. Pyroptosis is distinct from other forms of cell death, especially apoptosis that is characterized by nuclear and cytoplasmic condensation and is elicited via activation of a caspase cascade. In pyroptosis, gasdermin D (GSDMD) acts as a major executor, while NLRP3 related inflammasome is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 35 publications
(35 reference statements)
4
83
1
2
Order By: Relevance
“…In addition to activation of the NLRP3 inflammasome, palmitic acid has also been shown to cause many cellular perturbations such as ER stress, decreased cellular viability, loss of mitochondrial membrane potential, and the induction of many inflammatory genes such as IL-6 and TNF [79,80]. Mechanistically, palmitic acid and other saturated fatty acids can be crystallized in macrophages, which causes lysosomal membrane rupture, a known NLRP3 inflammasome trigger [76].…”
Section: Fatty Acid Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to activation of the NLRP3 inflammasome, palmitic acid has also been shown to cause many cellular perturbations such as ER stress, decreased cellular viability, loss of mitochondrial membrane potential, and the induction of many inflammatory genes such as IL-6 and TNF [79,80]. Mechanistically, palmitic acid and other saturated fatty acids can be crystallized in macrophages, which causes lysosomal membrane rupture, a known NLRP3 inflammasome trigger [76].…”
Section: Fatty Acid Saturationmentioning
confidence: 99%
“…In contrast, oleic acid inhibits and even mitigates the effects of palmitic acid, such that the treatment of macrophages with oleic acid inhibits IL-1β release in a dose-dependent manner [76]. Additionally, in HepG2 cells, oleic acid is able to decrease NLRP3 inflammasome activation and pyroptosis by reducing ER stress to counteract the effects of palmitic acid [80].…”
Section: Fatty Acid Saturationmentioning
confidence: 99%
“…50 Regarding liver function, administration of oleic acid has been shown to inhibit ER stress, alleviating hepatocellular lipotoxicity. 51 Similarly, inhibiting IRE1a-mediated inflammasome activation prevents the progression of NAFLD to steatohepatitis. 52 These discoveries paved the way to establishment of drugmediated therapies targeting the ER stress response (caspase-1, IRE1a, or acetyl-coenzyme A carboxylase inhibitors) to slow down the development of liver disease, and despite the fact that hypernutrition concurs with ER stress to promote hepatic tumorigenesis, 53 therapeutic nutritional approaches remain to be developped in this regard.…”
Section: Novel Concepts In Metaflammation the Nlrp3 Inflammasome: A Smentioning
confidence: 99%
“…115 In the liver, replacement of SFAs with MUFAs reduced hepatic GSDMD/-N, caspase-1, and p20 levels, indicating attenuation of NLRP3 activation. 51 Furthermore, in vivo saturated fat diet displays increased hepatic inflammation with increased serum amyloid A1 (SAA1) protein expression paired with reduced cholesterol transport compared with the low-fat diet control but not with monounsaturated fat diet. 87 In humans, a diet high in MUFAs decreases liver fat in both prediabetes and T2D compared with an isocaloric highcarbohydrate and high-fiber diet.…”
Section: Dietary Elements That May Counteract Metaflammation Mufas Anmentioning
confidence: 99%
“…Our study found that both PA and OA induced NAFLD via induction of PPARs, SREBP, ACC, ACOX, and FAS, which corresponds with previous reports that PA and OA disturbed lipid metabolism and induced NAFLD in HepG2 cells. 28,29 In one study, PA impaired cell viability and disturbed lipid metabolism in HepG2 cells, but OA robustly rescued cells from cell death by inhibition of endoplasmic reticulum stress and pyroptosis. 28 Moreover, in another study, OA reduced PA-induced oxidative stress, endoplasmic reticulum stress, and mitochondrial dysfunction in rat hepatocytes.…”
Section: Pa-induced Nafld In Hepg2 Cellsmentioning
confidence: 99%